Extracurricular Management in Developing Student Creativity at SMPN 96 South Jakarta - Alivia Dewi Nurochmah (CV. Kayaswara, 2025)
Extracurricular activities will not be successful if they are not properly managed by the school. Effective extracurricular management can not only support the success of extracurricular programs, but can also support the success of education as a whole. This research uses a descriptive method with a qualitative approach using data collection techniques such as observation, interviews, and documentation. The results of this study discuss the management, aspects, and foundation of extracurricular activities at SMPN 96 South Jakarta. First, the management of extracurricular activities at SMPN 96 South Jakarta includes planning, such as holding work meetings to discuss things that will be done in extracurricular activities for a semester and determining the types of extracurricular activities that will be held. Then the implementation is carried out during the period of introduction to the school environment, which aims to attract new students. In addition, the evaluation emphasizes student attendance and independence, and rewards students who excel. Second, the aspects of creativity in SMPN 96 South Jakarta are not only seen from students' satisfaction, but also provide opportunities for students to develop their skills. Third, the basis for developing the creativity of SMPN 96 South Jakarta students through extracurricular activities in the form of developing ideas.